The current information in nutrition therapy of phenylketonuria - Köseoğlu, Sabiha Zeynep Aydenk; Çelikel, Seda (Osman SAĞDIÇ, 2020)
Phenylketonuria (PKU) is one of the most common congenital metabolism disorders. In this disease, due to the defect in the phenylalanine hydroxylase enzyme made in the liver, phenylalanine cannot follow the tyrosine pathway and the symptoms of phenylalanine metabolites occur in body tissues, organs and body fluids. Nutritional therapy is applied in the treatment of the disease depending on the type of PKU. The purpose of nutritional therapy is to minimize the amount of phenylalane taken with nutrients and to keep the level of blood phenylale within normal limits. For this reason, a special nutrition program is applied throughout the life from the newborn period. The first step in the diagnosis of PKU is to determine the level of plasma phenylalanine with the blood sample taken from the heel of the newborn. Different types of hyperphenylalaninemias are seen as a result of phenylalanine hydroxylase enzyme and tetrahydrobiopterine (BH4) metabolism disorder. In the formation of BH4 cofactor defects, there is a defect in the metabolism of tetrahydrobiopterin, and its findings are different from classical PKU. In addition to the proper nutrition program, large neutral aminoacids (LNAA) and sapropterin (a synthetic form of BH4) are used in the treatment, according to the results of new studies. In classical PKU, when there is no medical nutrition treatment specific to the disease, many clinical findings such as mental retardation, skin-hair pigmentation disorders, growth retardation, microcephaly, epilepsy, behavioral disorders, hyperactivity and anxiety can be seen. In order for the symptoms associated with PKU to decrease and individuals with PKU to live a healthier life, they should comply with dietary treatment that includes protein-restricted, high-fat and carbohydrate-containing foods except for vegetables and fruits limited from phenylalanine Essential protein sources should be provided with special formulas with added tyrosine and essential amino acids and foods enriched with vitamins and minerals that may be deficient. However, the implementation of an effective nutrition therapy is possible by providing communication between the healthcare team and the family and introducing the disease to the family, and training in the development and treatment of the disease.
Keywords: Phenylketonuria; Phenylalanine; Phenylalanine hydroxilase; Tetrahydrobiopterin